KELENGKAPAN FORMULIR ASSESMEN MEDIS RAWAT JALAN DI RSUD TONGAS: Completeness of The Outpatient Medical Assessment Form at Tongas Hospital - Ikawati, Fita Rusdian; Rauf, Abdur; Nisak, Hoyrun (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
One effort to improve the quality of health services is by improving the quality of medical record services, including completeness and accuracy in providing information for health service needs. The completeness of filling out the outpatient medical assessment form at Tongas Regional Hospital, Probolinggo, still contains incomplete medical record forms, which affects patient information and routine reports made by medical records officers. The aim of this research is to identify the percentage of completeness of outpatient medical assessments at Tongas Probolinggo Regional Hospital. This type of research uses quantitative methods based on a descriptive approach, data collection techniques use random sampling techniques, this technique is used to take samples randomly and come from members of the population and data was collected using observation and literature review techniques using the Slovin formula with the results of 92 medical record forms. The results of the completeness of filling out outpatient medical assessments at Tongas Probolinggo Regional Hospital from 92 medical records taken in January 2024 showed a percentage of completeness of 95% and incompleteness of 5%.